2022
DOI: 10.3390/molecules27092940
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyridinium Based Ionic Liquid Promoter for Aqueous Knoevenagel Condensation: Green and Efficient Synthesis of New Derivatives with Their Anticancer Evaluation

Abstract: Herein, a distinctive dihydroxy ionic liquid ([Py-2OH]OAc) was straightforwardly assembled from the sonication of pyridine with 2-chloropropane-1,3-diol by employing sodium acetate as an ion exchanger. The efficiency of the ([Py-2OH]OAc as a promoter for the sono-synthesis of a novel library of condensed products through DABCO-catalyzed Knoevenagel condensation process of adequate active cyclic methylenes and ninhydrin was next investigated using ultimate greener conditions. All of the reactions studied went c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Even the heterocycles with nitrogen that are now employed in ILs are typically found in APIs or their precursors. Nayl et al reported the use of pyridinium-based dihydroxy ionic liquid ((Py-2OH) OAc) to improve the synthesis process and yield more potent anticancer compounds [ 90 ].…”
Section: Ionic Liquid-based New Active Pharmaceutical Ingredientsmentioning
confidence: 99%
“…Even the heterocycles with nitrogen that are now employed in ILs are typically found in APIs or their precursors. Nayl et al reported the use of pyridinium-based dihydroxy ionic liquid ((Py-2OH) OAc) to improve the synthesis process and yield more potent anticancer compounds [ 90 ].…”
Section: Ionic Liquid-based New Active Pharmaceutical Ingredientsmentioning
confidence: 99%
“…65,69 Pyridinium, ammonium, and other ILs have also been reported to have anticancer activity. 120–122 Aljuhani et al showed anticancer activities of a series of pyridinium ILs on two lung cancer cell lines (A549 and H-1229), and the maximum rate of proliferation inhibition was 99.69%. 123 Bourakadi et al evaluated the antitumor activity of a series of 3-methyl-1-alkyl-2-(thiazol-4-yl) benzimidazol-3-ium ILs against four human tumor cell lines: HT29 (colon), K652 (Leukemia), MDA-MB231, and SKBR3 (breast) and established the antitumor prospect of ILs based on thiabendazole.…”
Section: Therapeutic Components and Mechanismmentioning
confidence: 99%
“…In light of our previous work on the synthesis of novel antitumor heterocycles [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and with consideration of the aforementioned results, a new sort of VEGFR-2 inhibitors has been developed as prospective anti-breast cancer agents by hybridizing the coumarin and 1,3-thiazole moieties, which have been found to inhibit kinases and have antiproliferative properties. In this study, we developed and synthesized new 3-thiazolhydrazinylcoumarins in an effort to enhance the target compounds’ synergistic pharmacological significance and assess their anti-breast cancer activity targeting VEGFR-2.…”
Section: Introductionmentioning
confidence: 99%